Peculiarities of defect generation under injection current in LEDs based on group‐III nitride3N nanostructures. Issue 8 (11th May 2015) - Shmidt, Natalia; Shabunina, Evgeniia; Usikov, Alexander; Chernyakov, Anton; Kurin, Sergey; Helava, Hikki; Makarov, Yuri; Seibt, M.
Abstract It has been demonstrated that, along with well‐known mechanisms of defect generation (DG) under injection current in fabricated UV‐ and commercial blue‐LED chips based on A3N nanostructures, other defect generation mechanisms are possible in local regions. Aging experiments performed simultaneously with analysis of evolution of I‐V characteristics at U < 2 V and spectral noise density dependences on current density, revealed DG with participation of multi‐phonon recombination of carriers in an extended defect system and local regions of random alloy fluctuations enriched by metallic atoms (Ga or In). (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)